London : water and the making of the modern city - Broich, John (History of the urban environment., 2013)
As people crowded into British cities in the nineteenth century, industrial and biological waste byproducts and then epidemic followed. Britons died by the thousands in recurring plagues. Figures like Edwin Chadwick and John Snow pleaded for measures that could save lives and preserve the social fabric. The solution that prevailed was the novel idea that British towns must build public water supplies, replacing private companies. But the idea was not an obvious or inevitable one. Those who promoted new waterworks argued that they could use water to realize a new kind of British society - a productive social machine, a new moral community, and a modern civilization. They did not merely cite the dangers of epidemic or scarcity. Despite many debates and conflicts, this vision won out - in town after town, from Birmingham to Liverpool to Edinburgh, authorities gained new powers to execute municipal water systems. But in London local government responded to environmental pressures with a plan intended to help remake the metropolis into a collectivist society. The struggle over these plans was joined by some of the most colorful figures of the late Victorian period, including John Burns, Lord Salisbury, Bernard Shaw, and Sidney and Beatrice Webb. As the author demonstrates in this book, the debate over how to supply London with water came to a head when the climate itself forced the endgame near the end of the nineteenth century.